2020
DOI: 10.4103/tcmj.tcmj_161_19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of raw vegan diet on periodontal and dental parameters

Abstract: Objectives: Macronutrients and micronutrients present in different types of diet could influence different aspects of both inflammatory and immune responses; thereby, diets could influence oral health and the periodontal condition. The raw vegan diet is a subset of vegetarianism in which only uncooked plant-derived foods are consumed. The present study's aim was to evaluate the effect of the raw vegan diet on periodontal and dental health parameters. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For example, omnivores seem to be more prone to dental caries and eventual loss of all teeth, and they also have worse periodontal health indices when compared to vegans and vegetarians, who, in turn, are more predisposed to dental erosion due to the highly acidic nature of their nutrition [39]. Atarbashi-Moghadam and colleagues came to similar conclusions as they found that raw vegans had better periodontal health indices when compared to controls, but just like Azzola and colleagues, they emphasized that vegan participants often exhibited better oral hygiene practices and overall healthier lifestyle choices [40]. Eberhard et al found that following a semi-vegetarian high-fat diet improved periodontal health indices when compared to an omnivorous higher-fat or higher-carbohydrate diet or a semi-vegetarian higher-carbohydrate diet, implying that the consumption of less meat and carbohydrates might benefit periodontal health [41].…”
Section: Discussionmentioning
confidence: 84%
“…For example, omnivores seem to be more prone to dental caries and eventual loss of all teeth, and they also have worse periodontal health indices when compared to vegans and vegetarians, who, in turn, are more predisposed to dental erosion due to the highly acidic nature of their nutrition [39]. Atarbashi-Moghadam and colleagues came to similar conclusions as they found that raw vegans had better periodontal health indices when compared to controls, but just like Azzola and colleagues, they emphasized that vegan participants often exhibited better oral hygiene practices and overall healthier lifestyle choices [40]. Eberhard et al found that following a semi-vegetarian high-fat diet improved periodontal health indices when compared to an omnivorous higher-fat or higher-carbohydrate diet or a semi-vegetarian higher-carbohydrate diet, implying that the consumption of less meat and carbohydrates might benefit periodontal health [41].…”
Section: Discussionmentioning
confidence: 84%
“…Staufenbiel et al used DMFT indices in their methodology to confirm their findings of vegetarians to have more erosion. 7 Atarbashi-Moghadam et al 8 suggest a lower pH could be due to a vegetarian diet, especially raw vegans, consuming more fruits and therefore causing an acidic oral environment.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Iran looked at how a raw vegan diet affected periodontal and dental variables [ 80 ]. A raw vegan diet includes only plant foods not heated above ~118 °F.…”
Section: Dietary Risk Factors For Periodontitis/periodontal Disease A...mentioning
confidence: 99%
“…A study conducted in Iran looked at how a raw vegan diet affected periodontal and dental variables [80]. A raw vegan diet includes only plant foods not heated above ~118 • F. The cohort included 59 raw vegans and 59 controls of mean age 47 ± 14 years; all were nonsmokers.…”
Section: Dietary Risk Factors For Periodontitis/periodontal Disease A...mentioning
confidence: 99%